2018
DOI: 10.1016/j.knosys.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Dual channel LSTM based multi-feature extraction in gait for diagnosis of Neurodegenerative diseases

Abstract: The performance of gait disturbances differ in various Neurodegenerative diseases (NDs), which is an important basis for the diagnosis of NDs. In the diagnosis, doctors can judge disease state by observing patients' gait features without quantification, such a subjective diagnosis has been seen as a problem because diagnostic results may differ among doctors. Moreover, there are some irresistible factors such as fatigue may effects diagnostic procedure. To make use of these observations, we build an automatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 23 publications
0
63
0
Order By: Relevance
“…In order to examine performance of the proposed algorithm, four literatures [18,19,22,24] are selected to compare the algorithm performance. [18,19,22,24] adopted PhysioNet Gait Dynamics in Neurodegenerative disease [26] which is the same as this study. [18] employed stance and swing intervals series of left and right foot to do the two-class classifications (including classification of ALS vs. HC, HD vs. HC and PD vs. HC).…”
Section: Classification Performance Comparison To Other Literature Bamentioning
confidence: 99%
See 2 more Smart Citations
“…In order to examine performance of the proposed algorithm, four literatures [18,19,22,24] are selected to compare the algorithm performance. [18,19,22,24] adopted PhysioNet Gait Dynamics in Neurodegenerative disease [26] which is the same as this study. [18] employed stance and swing intervals series of left and right foot to do the two-class classifications (including classification of ALS vs. HC, HD vs. HC and PD vs. HC).…”
Section: Classification Performance Comparison To Other Literature Bamentioning
confidence: 99%
“…[18] employed stance and swing intervals series of left and right foot to do the two-class classifications (including classification of ALS vs. HC, HD vs. HC and PD vs. HC). [22] utilized two kinds of data as input, gait pattern data (stance and swing intervals series of left and right foot) and gait force data (vGRFs). Two-class classification including HC vs. ALS, HC vs. HD, HC vs. PD and NDDs vs. HC were compared using LOOCV as the cross validation.…”
Section: Classification Performance Comparison To Other Literature Bamentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to show a correlation between the severities of disease and the analytical results. Most research articles have demonstrated the difference between the disease groups and the healthy controls [ 26 , 27 ]. Only one paper gave details of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In [8], it is emphasized that with current methods, the diagnosis of Parkinson's disease tends to be subjective, for this reason a Kinect sensor [9] is used as a support for the diagnosis of Parkinson's, seeking to capture by means of this, the movement of patients, the movement of patients, extracting characteristics such as amplitude and frequency of movement, which are important for physicians to make a correct diagnosis of this disease. In [10], it is mentioned that currently for the detection and identification of neurodegenerative diseases, physicians tend to analyze the progress of patients, in this case, they focus on the detection of Parkinson's disease, Huntington and amyotrophic lateral sclerosis, implementing a type of RNN called LSTM, achieving a 95.67% accuracy in the identification of the gaits.…”
Section: Introductionmentioning
confidence: 99%